Burn injuries among paediatric patients treated at Mexican public hospitals: a retrospective cohort analysis of nationwide hospitalisation data - Taylor Wurdeman; John G Meara; Tanujit Dey; Tarsicio Uribe-Leitz; Jose Antonio Garcia Garcia; Diana D. Del Valle; Kevin Ashi; Jacques Bistre Varon; Juan Carlos Angulo-Lozano; Jaime Shalkow-Klincovstein (BMJ Global Health)
Introduction Paediatric burns are a leading cause of mortality among Mexican children, yet comprehensive national data are scarce. This retrospective cohort study provides an epidemiological analysis of paediatric burn injuries in Mexico using a nationwide hospitalisation database.Methods We conducted a retrospective cohort analysis of all paediatric burn patients aged 0–18 years (ICD-10 codes: T200–T329) who were hospitalised in the Mexican public sector using the Ministry of Health’s hospital discharge database for 2016, 2018 and 2020. We used descriptive statistics, and logistic and negative binomial regressions to examine associations with mortality, in-hospital infection rates and hospital length of stay. To explore associations between our outcomes and poverty indexes, we integrated state-level poverty data and the corresponding Gini coefficient (a measure of income inequality). In-hospital infections were identified from a categorical variable, indicating whether an in-hospital infection occurred. Additionally, we compared incidence rates and aetiology across states.Results We identified 11 080 paediatric burns. Most injuries involved males (60%, n=6659), predominantly children under 5 (55.8%, n=6186). Scalds were the most prevalent aetiology (46.5% n=5153). The overall infection rate was 1.5% (n=168), with electrical burns having the highest rate (1.97%, n=9). Mortality was 0.6% (n=65 cases), with the highest rate in firework-related injuries (1.6%, n=5). The majority (66.6%) of firework-related burns occurred during the holiday months of December and January. Longer hospital stays were significantly associated with in-hospital infections (incidence rate ratio (IRR)=2.52, p<0.01) and higher Gini coefficient (IRR=1.91, p=<0.01). In-hospital infection was significantly associated with increased mortality (OR=5.88, p=<0.01).Conclusions Paediatric burn injuries in Mexico are a critical public health issue, with children under 5 years old being the most vulnerable, and scalds being the predominant aetiology in this age group. This study underscores the need for targeted public health interventions and implementation of burn prevention programmes and regulations, especially regarding scald and firework injuries.